PP.20.28: KINETICS OF CHANGES IN AORTIC STIFFNESS AFTER SUCCESSFUL KIDNEY TRANSPLANTATION AFTER 2-YEARS. (June 2015) - Agharazii, M.; Turgeon, D.; Lesage, J.; Fortier, C.; Ignace, S.; Marquis, K.; De Serres, S.A.; Coté, I.; Houde, I.; Mac-Way, F.
Abstract : Objective: We have previously shown that there is a blood pressure independent reduction in aortic stiffness as early as 3 months after successful a kidney transplantation (KTx). The purpose of the present study is to examine the effects of KTx on changes in aortic stiffness after 2 years of follow-up. Design and method: In this prospective, longitudinal observational study, we studied hemodynamic and biological parameters prior to KTx and 3, 6 and 24 months after a KTx in 59 dialysis patients. Aortic stiffness was measured by carotid-femoral pulse wave velocity (cf-PWV). A successful kidney transplant was defined by an estimated eGFR of 45 or more mL/min/1.73 2 at the time of the measurement of aortic stiffness. A GEE model was used to take into account the repeated measures of aortic stiffness and mean blood pressure. Values are reported as mean ± SEM unless otherwise specified. Results: The mean age was 48 ± 14 years, with 70% male, 20% with cardiovascular disease and 25% diabetes. After adjusting for mean blood pressure, cf-PWV decreased significantly from 11.2 ± 0.33 to 10.3 ± 0.30 by 3 months (P = 0.042), but it increased to 10.8 ± 0.31 and 11.2 ± 0.33 (m/s) by 6 and 24 months (P = NS versus preKTx). The rate of progression of aortic stiffness beyond 3 months was 0.248 m/s/year. Figure. No caption available. Conclusions: After an initial improvement of aortic stiffness, there is a progression of aortic stiffness that is numerically lower than what has been previously been reported in dialysis population.